The FLP Microsatellite Platform Flight Operations Manual - Eickhoff, Jens.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book represents the Flight Operations Manual for a reusable microsatellite platform - the "Future Low-cost Platform" (FLP), developed at the University of Stuttgart, Germany. It provides a basic insight on the onboard software functions, the core data handling system and on the power, communications, attitude control and thermal subsystem of the platform. Onboard failure detection, isolation and recovery functions are treated in detail. The platform is suited for satellites in the 50-150 kg class and is baseline of the microsatellite "Flying Laptop" from the University. The book covers the essential information for ground operators to controls an FLP-based satellite applying international command and control standards (CCSDS and ECSS PUS). Furthermore it provides an overview on the Flight Control Center in Stuttgart and on the link to the German Space Agency DLR Ground Station which is used for early mission phases. Flight procedure and mission planning chapters complement the book. .
Keywords: Aerospace engineering; Astronautics; Computers, Special purpose; Electronics; Aerospace Technology and Astronautics; Special Purpose and Application-Based Systems; Electronics and Microelectronics, Instrumentation